Pengaruh Rasio Keuangan dan Value Added Human Capital Terhadap Profitabilitas Perusahaan Infrastruktur - Oktora, Boni; Abdullah, Abdullah (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
The purpose of this research is to test and close the knowledge gap on how Current Ratio, Cash Turnover Ratio, Debt to Asset Ratio, Total Asset Turnover and Value Added Human Capital affect profitability determined by Return on Assets in infrastructure companies listed on the Indonesian stock exchange in 2014-2023. This research uses quantitative methods with panel data regression analysis. Purposive sampling was used to select 25 companies as samples, resulting in a total of 250 observations. After considering outlier statistics, 182 observations remain that can be used in the analysis. The regression results show that CR has no significant effect on ROA with a p-value of 0.9174, while CTR shows a significant but negative effect with a p-value of 0.0044. DAR also has a significant negative effect with a p-value of 0.0000. In contrast, TATO and VAHU have a significant positive effect on ROA with the same p-value of 0.0000. The study emphasizes that efficient asset management and optimization of human resources can increase a company's profitability, while high liquidity and dependence on debt need to be managed wisely to prevent adverse impacts on financial performance.